2014
DOI: 10.17511/ijphr.2014.i1.06
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia: a burden for world health

Abstract: Anemia is the world's second leading cause of disability and is responsible for about 1 million deaths a year, of which threequarters occur in Africa and South-east Asia. India is among the countries with highest prevalence of anemia and accounts for the largest number of anemic persons in the world. The magnitude of reduction in the prevalence of anemia during nineties in India is lower than that in neighboring south and south East Asian countries. Strategy to prevent and correct iron deficiency anemia, must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…A review article about iron deficiency Anemia, as a burden for world health (Kumar & Sagar, 2014), concluded that iron deficiency anemia in adolescent girls and pregnant women can adversely affect the cognitive performance, behavior, performance of adolescents and physical growth of infants, preschool and school-age children. Anemia affects immune status and morbidity from infections of all age groups.…”
Section: Anemia Is Classified As Iron Deficiency Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…A review article about iron deficiency Anemia, as a burden for world health (Kumar & Sagar, 2014), concluded that iron deficiency anemia in adolescent girls and pregnant women can adversely affect the cognitive performance, behavior, performance of adolescents and physical growth of infants, preschool and school-age children. Anemia affects immune status and morbidity from infections of all age groups.…”
Section: Anemia Is Classified As Iron Deficiency Anemiamentioning
confidence: 99%
“…It revealed that diarrhea, stunting, household food insecurity, dietary diversity, and age were identified as predictors of anemia in children aged 6 -23 months. A cross-sectional survey carried out in low and middleincome countries (Kumar & Sagar, 2014) found that educational status, wealth status, family size, media exposure, and residence were common factors significantly associated with anemia in pregnant and non-pregnant women. According to the study, mode lIII was selected and all the factors with p-values <0.001 were considered predictors of anemia.…”
Section: Causes Of Anemiamentioning
confidence: 99%
“…Anemia is also independently known to have a relationship with cognitive decline in terms of intelligence, impaired language coordination, skills, poor attention, and decreased memory and learning ability (Yehuda et al, 2009). In fact, according to Kumar (2014), anemia is the second highest cause of disability in the world, because anemia can cause various kinds of complications, including decreased endurance, cognitive impairment, stunted growth, decreased activity, and changes in behavior…”
Section: Introductionmentioning
confidence: 99%